Pengaruh Komitmen Organisasi Dan Komunikasi Terhadap Kinerja Karyawan Outsourcing Pada PT Mega Armada Sudeco (Tunas Auction) Bekasi, Jawa Barat - Nur Nadhifah; Noryani Noryani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of organizational commitment and communication on the performance of outsourcing employees at PT. Mega Armada Sudeco. A quantitative approach was employed, using a saturated sampling technique with a total of 75 respondents. Data analysis included validity testing, reliability testing, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficient analysis, coefficient of determination, and hypothesis testing using SPSS version 26. The results indicate that organizational commitment has a significant effect on employee performance, with the regression equation Y = 1,929 + 0,599X1, a correlation coefficient of 0,693 indicating a strong relationship, and a coefficient of determination of 48%. Hypothesis testing shows that tvalue > ttable (8,211 > 1,993), thus H₀ is rejected and H₁ is accepted. Communication also significantly affects employee performance, with the regression equation Y = 1,153 + 0,754X2, a correlation coefficient of 0,724 indicating a strong relationship, and a coefficient of determination of 52,4%. The tvalue > ttable (8,967 > 1,993), leading to the rejection of H₀ and acceptance of H₂. Simultaneously, organizational commitment and communication significantly influence employee performance. The multiple regression equation obtained is Y = 1,105 + 0,287X1 + 0,488X2, with a correlation coefficient of 0,754, indicating a very strong relationship. The coefficient of determination is 56,9%, while the remaining percentage is influenced by other factors. The F-test shows that Fvalue > Ftable (47,479 > 3,124), meaning H₀ is rejected and H₃ is accepted. Thus, both variables jointly have a significant effect on the performance of outsourcing employees